Analisis Perbandingan Rantai Distribusi Beras Organik di Desa Candingasinan, Kecamatan Banyu Urip dan Desa Ringgit, Kecamatan Ngombol, Kabupaten Purworejo - Rahmawati, Raina, Ir. Taryono,M.Si (2017)
The awareness of health and environmental sustainibility have change people paradigme to consume healthy food, for example organic rice. Demand for organic rice grows and creats a market system that form the distribution chain from producer, distributor, untul it reaches the consumer. This study aims to determine the productivity of organic rice, the dominant factor that can influence the production and analyze the disstribution chain of organic rice in the research area. The data was obtained from interviews and questionnaires for farmers (producers) and retailerabout organic farming and its marketing by using snowball sampling method with the farmers as the starting point. The data was analyzed by using comprehensive and descriptive quantitative analysis method. The results showed that the level of organic rice productivity in Ringgi village is 10,5 tons/ha. It is higher than Candingasinan village that only produce 8,5 tons/ha. The most influential factor that increase the organic rice produstion is rainfall and management. Organic rice distibution chain formed in Candingasinan village is producer-consumer and producer-retailer-consumer. Its market has reach some district in Purworejo regency. Organic rice distribution chain formed in Ringgit village has 2 channels, such as the producer-warehouse-retailer-consumer and producer-warehouse-consumer. Its market has reach Purworejo, Jakarta, Bekasi, Tangerang, Yogyakarta and Surabaya.